2016
DOI: 10.3390/nu8050281
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Metabolic Health: The Potential Beneficial Effects of a Medium Chain Triglyceride Diet in Obese Individuals

Abstract: Obesity and associated metabolic complications, such as non-alcoholic fatty liver disease (NAFLD) and type 2 diabetes (T2D), are in constant increase around the world. While most obese patients show several metabolic and biometric abnormalities and comorbidities, a subgroup of patients representing 3% to 57% of obese adults, depending on the diagnosis criteria, remains metabolically healthy. Among many other factors, the gut microbiota is now identified as a determining factor in the pathogenesis of metabolica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 159 publications
(230 reference statements)
2
73
0
4
Order By: Relevance
“…There are: (1) increased caloric intake from indigestible polysaccharides, combined with effect on hepatic de novo lipogenesis via carbohydrate and sterol response-element binding proteins; (2) enhanced cellular uptake of fatty acids and storage of triglycerides in adipocytes via suppression of intestinal expression of fasting-induced adipocyte factor which is circulating inhibitor of lipoprotein lipase; (3) suppression the skeletal muscle fatty acid oxidation through a metabolic pathway involving phosphorylation of adenosine monophosphate-activated protein kinase; and (4) interaction between short chain fatty acids products of microbial fermentation of dietary polysaccharides and G-protein-coupled receptor 41 which results in increased levels of enteroendocrine cell-derived hormone PYY, thus, reducing gut motility with subsequently increased intestinal transit time and absorption rate of short-chain fatty acids [79]. Microbiota can also promote obesity and metabolic syndrome by inducing low-grade inflammation [7, 10]. Currently, gut microbiota is increasingly considered as a “metabolic organ” greatly affecting the organism’s metabolism [11].…”
Section: Introductionmentioning
confidence: 99%
“…There are: (1) increased caloric intake from indigestible polysaccharides, combined with effect on hepatic de novo lipogenesis via carbohydrate and sterol response-element binding proteins; (2) enhanced cellular uptake of fatty acids and storage of triglycerides in adipocytes via suppression of intestinal expression of fasting-induced adipocyte factor which is circulating inhibitor of lipoprotein lipase; (3) suppression the skeletal muscle fatty acid oxidation through a metabolic pathway involving phosphorylation of adenosine monophosphate-activated protein kinase; and (4) interaction between short chain fatty acids products of microbial fermentation of dietary polysaccharides and G-protein-coupled receptor 41 which results in increased levels of enteroendocrine cell-derived hormone PYY, thus, reducing gut motility with subsequently increased intestinal transit time and absorption rate of short-chain fatty acids [79]. Microbiota can also promote obesity and metabolic syndrome by inducing low-grade inflammation [7, 10]. Currently, gut microbiota is increasingly considered as a “metabolic organ” greatly affecting the organism’s metabolism [11].…”
Section: Introductionmentioning
confidence: 99%
“…We solved the crystal structure of the PPARγ LBD bound to edaglitazone at the orthosteric pocket, which unexpectedly revealed a bacterial MCFA cobound to the alternate site. MCFAs are not only present in bacteria; they are also dietary mammalian natural PPARγ ligands obtained from foods such as oils and dairy products (31) that display high serum concentrations (µM-mM) and activate PPARγ transcription, regulate the expression of PPARγ target genes, and influence cellular differentiation, adipogenesis, and insulin sensitization in mice (15,32,33). The cobound MCFA provides a "ligand link" to the flexible Ω-loop, and crystal structures of PPARγ bound to covalent orthosteric antagonists revealed that synthetic ligands extensions within the orthosteric pocket can push fatty acid cobinding modes towards the Ω-loop.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to carbohydrates and lipids, the relative amount of dietary nitrogen was found to fundamentally shape the gut microbiota structure and influence healthy host-microbiome outcomes (32,33). Some minor molecules in diets, such as polyphenols, flavonoids and medium-chain triglycerides, are also able to shift gut microbiota and consequently alleviate obesity (34)(35)(36)(37)(38)(39).…”
Section: Influence Of Diet Quality On Gut Microbiota Interventionmentioning
confidence: 99%